Biomarkers and Mechanism Analysis for Polygoni Multiflori Radix Preparata-Induced Liver Injury by UHPLC-Q-TOF-MS-Based Metabolomics. (23rd November 2021) - Wang, Liming; Wang, Zhida; Xing, Yanchao; Liu, Erwei; Gao, Xiumei; Wang, Linlin; Fu, Zhifei
Abstract : Background . Polygonum Multiflorum Radix Preparata (PMP), prepared from Polygonum multiflorum Thunb. (PM), is traditionally valued for its liver and kidney-tonifying effects. However, the previous studies showed that PMP was hepatotoxic, which limited its clinical use. Unfortunately, the potential hepatotoxic ingredients and the molecular mechanism are still uncertain. Objective . The aim of this study was to find out potential biomarkers of hepatotoxicity using metabolomics profile. Materials and Methods . 60% ethanol extract of PMP (PMPE) was prepared. Subsequently, an untargeted metabolomics technology in combination with ROC curve analysis method was applied to investigate the alteration of plasma metabolites in rats after oral administration of PMPE (40 g/kg/d) for 28 days. Results . Compared to the control group, the significant difference in metabolic profiling was observed in the PMPE-induced liver injury group, and sixteen highly specific biomarkers were identified. These metabolites were mainly enriched into bile acids, lipids, and energy metabolisms, indicating that PMPE-induced liver injury could be related to cholestasis and dysregulated lipid metabolism. Conclusions . This study is contributed to understand the potential pathogenesis of PMP-induced liver injury. The metabonomic method may be a valuable tool for the clinical diagnosis of PMP-induced liver injury.